Promoting Learner Autonomy through University E-Learning Platforms in an English for Specific Purposes (ESP) Course - Ledy Nur Lely; Welliam Hamer (Universitas Mathla'ul Anwar Banten, 2025)
This study evaluates how a university online learning platform supports learner autonomy among first-year English Department students at Sultan Ageng Tirtayasa University taking an English for Specific Purposes course. Using a mixed-method design, the study combines pre-test and post-test data with students’ reflections and questionnaire results. A total of 75 students (40 from Class C and 35 from Class D) participated in a 16-week online program that focused on vocabulary, reading comprehension, and scientific writing. The results show clear improvement in students’ English abilities, supported by higher post-test scores. Qualitative data also show that students became more independent, especially in planning, goal setting, and managing their study time. Overall, the results suggest that a well-designed online platform can effectively support both language learning and learner autonomy for English majors in specific fields.